Oral lesions in elderly denture wearers: a scoping review protocol (Research, Society and Development, 2021)
The aging of the population raises the need for special health care. Edentulism, for example, is an oral condition that affects mainly the elderly, and it is common to use dental prostheses that often generate oral lesions. This protocol proposes a scoping review on the prevalence of oral mucosa lesions due to the use of dental prostheses in the elderly population. Thus, the objective of this protocol is to present the methodology that will be adopted, according to the recommendations of the Joanna Briggs Institute for scoping reviews, and this document was previously registered in the Open Science Framework repository. The search strategy will be designed to identify possible sources of evidence published in the following databases: Cochrane, PubMed via MEDLINE, LILACS, Web of Science, and Scopus. With regard to the grey literature, searches will be made via Google Scholar. The following controlled vocabulary descriptors will be used Health Science Descriptors/Medical Subject Headings were used: aged/idoso, dental prosthesis/prótese dentária and oral manifestations/manifestações bucais, their synonyms and spelling variations. The PCC (Population, Concept, Context) strategy will serve as the basis for developing the research question and defining the inclusion and exclusion criteria. The results of the proposed scoping review should show the factors that influence the prevalence of oral mucosal lesions in elderly people who use dental prostheses.